Compromisso popular da universidade na educação científica: percepções docentes na UFSCar de São Carlos - Leda, Leticia Maria (Universidade Federal de São Carlos, 2025)
The research aims to understand how UFSCar has materialized its commitment to the popular dimension in scientific education from the perspective of professors in the Biological Sciences, Physics, and Chemistry undergraduate teaching programs, considering the material, political, and social conditions that influence their practices and their role in social transformation. Grounded in the contributions of Paulo Freire and Marilena Chauí, the study examines how university autonomy is affected by neoliberal policies that subordinate education to market interests and how public universities can promote critical and emancipatory education in the face of neoliberal pressures. In this context, academic research has increasingly aligned with the concept of technoscience, characterized by the subordination of science to market logic, which influences not only research topics but also initiatives within the university itself (such as business incubators and public-private partnerships). Data were collected through semi-structured interviews with professors, and the analysis was conducted using Discursive Textual Analysis (DTA), which enables a deeper understanding of the contradictions and challenges identified. The results indicate that, while professors acknowledge the university’s commitment to the popular dimension, there are different perspectives on how this commitment is realized. The research highlights the need to strengthen institutional policies that foster dialogue between the university and society, ensuring the necessary conditions for the popular commitment of the university to be effectively translated into consolidated practices.
The university's popular commitment in science education: professors's perceptions at UFSCar São Carlos
Keywords: Compromisso Popular; Universidade pública; Percepção de professores; Função social; Popular commitment; Public university; Professor’s perception; Social function; CIENCIAS HUMANAS::EDUCACAO